Classical swine fever virus employs the PERK- and IRE1-dependent autophagy for viral replication in cultured cells. Issue 1 (1st January 2021) - Zhu, Erpeng; Wu, Huawei; Chen, Wenxian; Qin, Yuwei; Liu, Jiameng; Fan, Shuangqi; Ma, Shengming; Wu, Keke; Mao, Qian; Luo, Chaowei; Qin, Yixian; Yi, Lin; et al.
ABSTRACT: Endoplasmic reticulum stress (ERS)-mediated autophagy is indispensable for modulation of replication and pathogenesis of numerous mammalian viruses. We have previously shown that classical swine fever virus (CSFV) infection induces ERS-mediated autophagy for maintaining viral replication both in vivo and in vitro, however, the underlying mechanism remains unclarified. Here we found that CSFV infection activates the PERK pathway-dependent complete autophagy to promote viral replication in cultured PK-15 and 3D4/2 cells. Likewise, our results also suggested the essential roles of the IRE1/GRP78-mediated complete autophagy in CSFV replication in vitro . Furthermore, we suggested that CSFV infection induces activation of the PERK and IRE1 pathway for potential immunoregulation via promoting transcription of proinflammatory cytokine ( IFN-γ and TNF-α ) genes in the CSFV-infected cells. Finally, pharmacological treatment of PERK- or IRE1-pathway regulators, and the corresponding SiRNAs interventions did not affect the viabilities of the cells, excluding the potential interference elicited by altered cell viabilities. Taken together, our results suggest that CSFV infection induces complete autophagy through activation of the PERK and IRE1 pathway to facilitate viral replication in cultured cells, and modulation of proinflammatory cytokines may be a potential mechanism involved in this event. Our findings will open new horizons for molecular mechanisms of sustainable replication and pathogenesis of CSFV, and lay a theoretical foundation for the development of ERS-autophagy-targeting therapeutic strategies for clinical control of CSF.